A study on feto-maternal outcome of intra hepatic cholestasis of pregnancy - Mitra, Binay; Maji, Debkalyan; Borse, D. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Intrahepatic cholestasis of pregnancy is one kind of the hepatic disorder which is unique to pregnancy. It is associated with many adverse pregnancy outcomes if doesn’t intervened at right time. It requires adequate clinico-biochemical correlation during management. Methods: A prospective observational study was conducted at multispecialty government zonal hospital. Total 137 IHCP patients were managed during the study period from 01 Jan 2017 to 30 Jun 2019. Incidence and pregnancy outcome in form of several maternal and fetal factors were analysed by appropriate statistical test using spps software version 20.0. Results: During the study period total 4872 patients were undergoing delivery and 137 patients were diagnosed with IHCP. The incidence of IHCP was 2.81%. Majority of cases 75 out 137 (54.74%) were nulligravida. Total 29.92% (41/137) cases were underwent LSCS delivery and of this 21.17% (29/137) were primary caesarean delivery. There were three still birth noted in IHCP study population. Total 28 cases (20.44%) of IHCP were presented with preterm labour. And NICU admissions of the study population were 32 new born babies (23.36%). 2.18% case of still birth was noted among study population. Conclusions: IHCP causes significant maternal and neonatal morbidity and is major contributor of preterm delivery, caesarean delivery, meconium stained liquor and NICU admission.